Conscious in two ways: Robert M. Doran remembers - Doran, Robert M. (Marquette studies in theology, 2021)
"Fr. Robert M. Doran is a model of what it means to teach and minister to others with the utmost humility, generosity, and compassion. The indelible impact of his mentorship will be felt for generations to come. This interview tells the story of his life, his intellectual autobiography and the challenges that contributed to his greatness"--